Community Structure of Benthic Algae in a Lotic Ecosystem, Karbala Province-Iraq (Baghdad Science Journal, 2025)
This study focused on benthic algae (epipelic and attached algae on concrete lining stream) in Bani-Hassan stream in Holly Karbala, Iraq. The qualitative and quantitative studies of benthic algae were done by collecting 240 samples from five sites in the study area for the period from December 2012 to November 2013. Also, the environmental variables of the stream were examined in term of temporary and spatial. The results showed that the stream was alkaline, hard, oligohaline and a well aerated. The total nitrogen to the total phosphorus (TN: TP) ratio indicates nitrogen limitation. 129 species of benthic algae belonging to 57 genera were identified. Bacillariophyceae (diatoms) was the predominant taxon (95 species) followed by Chlorophyceae (16 species), Cyanophyceae (14 species), Euglenophyceae (3 species) and Pyrophyceae (one species). Some genera were found throughout the study period: Nitzschia, Navicula, Cymbella, Gomphonema, Surirella, Cocconeis, Aulacoseira, Oscillatoria, Lyngbya, Spirulina, and ? Scenedesmus. Site 3 recorded the highest total number of algae in spring 2013, and the lowest total number was at site 5 in Autumn 2013. The chlorophyll-a concentration did not match the total number of algae.